Intraoperative iodinated contrast swallow with CT-scan delayed control for detection of early complications in laparoscopic gastric bypass: A case series of 260 cases. (2017) - Consalvo, Vincenzo; Salsano, Vincenzo; Sarno, Gerardo
Abstract: Background: Laparoscopic Roux en Y Gastric Bypass (LRYGB) is a technically challenging operation with potentially severe surgical complications. A large number of tests have been proposed in order to early identify them in the immediate post-operative period but none was completely satisfactory. Actually, there is no data concerning the use of an early diagnostic protocol based on an intraoperative contrast swallow and a CT- scan at 48 h. Methods and analysis: From may 2012 to February 2017, 281 patients underwent LRYGB. A 40 cc of iodinated water-soluble contrast (Gastrografin ® or Telebrix ® ) was administered through the orogastric tube 5 min after the blue methylene test while 48 h later, they underwent a CT-scan. The early detection of the contrast liquid in the alimentary or bilio-pancreatic limb, in proximity of it or free in the abdomen were considered signs of bowel obstruction or anastomotic leak. Results: 220 were test negative while 35 patients were positive and a second look was carried out successfully. Considering our data, sensitivity was 0, 97 (CI 95% = 91, 85–100%) while specificity stated at 0, 98 (CI 95% = 96, 48–99, 95%). The positive predictive value was 0, 89 (CI 95% = 80, 22–99, 27%) and the negative predictive value was 0, 99 (CI 95% = 98, 66–100%). Conclusions: This study gives a contribute to the existing issue of fast track in bariatric surgery for the early diagnosis of complications and patients' readmission or non-discharge. In conclusion, the use of intraoperative iodinated water soluble contrast swallow and abdominal CT-scan at 48 h was a safe and accurate test in order to detect and treat any potential early surgical complication in LRYGB. Highlights: 281 patients underwent Laparoscopic Roux en Y gastric bypass (LRYGB). 20 cc of iodinated contrast was administered through the orogastric tube and 48 h later, they underwent a CT-scan. Sensitivity was 0, 97 (CI 95% = 91, 85–100%) while specificity stated at 0, 98 (CI 95% = 96, 48–99, 95%). It was a safe and accurate test in order to detect any potential early surgical complication in LRYGB.